2023
DOI: 10.1123/ijatt.2022-0012
|View full text |Cite
|
Sign up to set email alerts
|

The Test–Retest Reliability and Minimal Detectable Change of the FitLight Trainer™

Abstract: Context: Reaction time is an indicator of cognitive function postconcussion and is an important measurement in return-to-play protocols. Current postconcussion assessments lack evidence regarding their reliability and do not simulate functional movement patterns and choice reactions that occur in sport performance. Objective: This study sought to establish the test–retest reliability of the FitLight Trainer™ in a nonconcussed, healthy population. Methods: Twenty-six healthy individuals from Bowling Green State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This finding is consistent with FG Team's report that FITLIGHT Trainer can help trainers to improve vital aspects of emerging performance, including speed, agility, acceleration capabilities, visual cognitive processing, reaction response, fluidity of movement, physical adaptation, motor skills, cognitive skills, concentration, ambient awareness, vertical lifting ability, multi-directional change and hand-eye coordination. The system also helps trainers track progress in injury recovery ( 37 , 38 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with FG Team's report that FITLIGHT Trainer can help trainers to improve vital aspects of emerging performance, including speed, agility, acceleration capabilities, visual cognitive processing, reaction response, fluidity of movement, physical adaptation, motor skills, cognitive skills, concentration, ambient awareness, vertical lifting ability, multi-directional change and hand-eye coordination. The system also helps trainers track progress in injury recovery ( 37 , 38 ).…”
Section: Methodsmentioning
confidence: 99%
“…FITLIGHT is a fast and cognitive training system that uses photo stimulus with a variety of training protocols ( 38 ). The FITLIGHT system can improve a range of motion, strength, coordination, body comprehension, agility, balance and neurocognitive disorders ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the evaluation of the extremity reaction time of the volleyball players, the Light Trainer Flash Light Exercise System ™ reaction time device was used (intraclass correlation: 0.89). 16 Packages are available from 4 to 32 spots. As part of our research, we had 2 packages of 8 spotlights, each with default software (Software version: 4.0.32).…”
Section: Eccentric Hamstring Muscle Strengthmentioning
confidence: 99%
“…The test was applied 3 times, after which the mean reaction time was calculated, and this was recorded together with the fastest reaction time. 16…”
Section: Eccentric Hamstring Muscle Strengthmentioning
confidence: 99%
“…A series of studies have concluded that the FitLight Trainer™ System [22] can be used as a training and evaluation tool with a high level of reliability, validity, versatility and portability in measuring simple and complex reactive time to visual stimuli in different categories of healthy populations of athletes and non-athletes [23][24][25]. The Fitlight Training System was used to study reactions to visual stimuli in physical education lessons, demonstrating that the use of these devices contributes to improving simple and complex reaction time in relation to the selective attention of primary school students [26,27].…”
Section: Introductionmentioning
confidence: 99%